Analysis of Motor Sharing (Online Transportation) Customer in Bandung. Case Study: Go-Jek in Bandung - Waruwu, Jenis Jaya; Adhiutama, Akbar (Journal of Business and Management, 2017)
Abstract— Globalization era makes the technology advancement more rapidly, this matter  can be seen from the number of internet users in the world will increasing each year  that reach until 200 to 300 million users per year. Internet usage is very diverse depending on the needs of user, for example is for an online business. Recently the online business was trended in Indonesia such as for online transportation. The online transportation business in Indonesia was booming like as the GO-JEK, the Bojek, the Wheel Line, the Blu-Jek, the Transjek, the PRO-JEK, the TEKNOJEK, the Bangjek, etc. The GO-JEK is a pioneer of online transportation in Indonesia, this matter can be seen by established of company is the first in Indonesia, the feature and the operational area also is wider than the other company. Certainly, the presence the online transportation or motor sharing in the midst society will influenced of lifestyle the peoples who live in urban areas to avoid the traffic. So, there much perception of user towards experienced in used the service. This research aims to analyze the online transportation especially in Bandung based on the user/customer perception towards the service online transportation like as GO-JEK. The researcher will analyze to make sure whether the issue from some news about GO-JEK is appropriate towards the result of this research or not. The researcher will analyze it with the three the theoretical basis: the first is Diffusion of Innovation to identify the adopter categories of user. The second is TAM & TPB combination to find out the factors acceptance the Go-JEK, and the last is SERVQUAL to identify the actual service quality of GO-JEK in Bandung based on user perception. Then, the researcher used the Correlation Coefficient Analysis method to correlate the above theories. Besides that, the researcher used SPSS (statistic packages for social science) to process the research questionnaire result. The result of research shows that the categories of GO-JEK user in Bandung consist as 8,3% as the innovators, 21,7% is the early adopters, 28,1% is the early majority, 26,9 is the late majority, and the last is 15% as the laggards. Overall TAM towards TPB, Diffusion of Innovation (DOI) towards TAM & TPB combination, DOI towards SERVQUAL variables, TAM & TPB towards SERVQUAL variable, and SERVQUAL variables have significant correlation in use the GO-JEK service in Bandung. Generally, the GO-JEK service quality in Bandung shows the high of level percentage based on user perspective. It means the result of the research it does not same with the research background which published by some media about the service of GO-JEK because media it cannot representative the service quality a company. Keyword: GO-JEK, online transportation, Diffusion of Innovation, TAM & TPB combination, Service Quality, Correlation Coefficient Analysis.